Chapter Archeologia subacquea in Liguria: un progetto integrato per la tutela e la valorizzazione - Trigona, Simon Luca (Proceedings e report, 2020)
The Soprintendenza of Liguria has always given a particular attention to underwater archaeology and still today it pursues clear and specific aims: design, build, manage and increase competences and technologies that can be able to contribute to the regional and cultural development. The experience reached in Liguria by many years, leaded our activities of protection, research and valorization in order to develop a network of integrated archaeological sites and naval museums. On land this project provides two new museums in the cities of Albenga and Imperia that will be connected with a series of exhibitions and conferences